Study on the Preparation and Characterization of Polypyrrole/Montmorillonite Conductive Composites - Zhou, Yuanyuan; Li, Song (Asian Journal of Chemistry, 2011)
Polypyrrole/montmorillonite composite were prepared by the in situ polymerization of pyrrole in the presence of montmorillonite. Infrared spectroscopy, thermogravimetric analysis, X-ray diffraction and transmission electron microscopy were used to characterize the composition and structures of composite materials, as well as test the conductivity of composite materials through four-probe technique. The preparation conditions of polypyrrole/montmorillonite conducting composites were optimized, the results showed that when the reaction lasted for 15 h in the ice bath, the amount of montmorillonite, FeCl3·6H2O and the dopant BSNa was 0.4 g/mL pyrrole, 9.1 g/mL pyrrole and 4.4 g/mL pyrrole, respectively. At the moment, the composite had the larger conductivity up to 56 S/cm. According to FT-IR spectroscopy, it showed that it did exist polypyrrole and montmorillonite in polypyrrole/montmorillonite composite system, which reprented that the montmorillonite certainly exhibited remarkable improvement in materials' properties when compared with virgin polypyrrole composites.